2019
DOI: 10.1038/s41598-019-40806-0
|View full text |Cite
|
Sign up to set email alerts
|

A join point regression analysis of trends in mortality due to osteoporosis in Spain

Abstract: Osteoporosis is a major health problem in terms of fracture probability and disability. The aim of this ecological study is to identify the temporal trends in osteoporosis mortality in Spain from 1999 to 2015. Data on the Spanish population and number of deaths due to osteoporosis were obtained from the Spanish National Institute for Statistics. Age-adjusted mortality rates were estimated. Join point regression was used to identify the years when changes in mortality s and annual percentage change in mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 60 publications
1
21
1
1
Order By: Relevance
“…A steady increase in the mortality rate was seen from 1999 to 2003, but in 2004, the rates declined throughout the remainder of the study period. The mortality rate was shown to decrease faster in older cohorts, especially women, similar to the present findings [ 29 ]. The mortality rate for those >65+ years demonstrated an inverted U-shape from 1999 to 2017 for the four census regions.…”
Section: Discussionsupporting
confidence: 91%
“…A steady increase in the mortality rate was seen from 1999 to 2003, but in 2004, the rates declined throughout the remainder of the study period. The mortality rate was shown to decrease faster in older cohorts, especially women, similar to the present findings [ 29 ]. The mortality rate for those >65+ years demonstrated an inverted U-shape from 1999 to 2017 for the four census regions.…”
Section: Discussionsupporting
confidence: 91%
“…39 On the other hand, female sex in our sample was associated with higher prevalence of depression, osteoarthritis, and osteoporosisfactors which may compromise results of the assessment of frailty components, that are also associated with increased mortality. [40][41][42] Our results indicate that in contrast to the frailty phenotype analyzed in older-old adults in other studies, the frailty phenotype in early-old adults does not encompass all significant risk factors for mortality and therefore may not be considered an index of global health. Thus, as other studies have also concluded, 43,44 frailty phenotype assessment adds important information to the comprehensive geriatric assessment, but it may not substitute for the CGA as a method of global health assessment in earlyold community-dwelling adults.…”
Section: Discussioncontrasting
confidence: 72%
“…This programme will use the annual prevalence and incidence rates and identify the years in which changes have occurred in the trend of IBDs (join points), and then, using exponentiating beta-coefficients of Poisson regression and subtracting 1, the Annual Percentage Change of these indicators will be calculated between the trend points at a 95% CI. The programme will also calculate the Average Annual Percentage Change (AAPC) for the entire study period 40 41…”
Section: Study Eligibility Criteriamentioning
confidence: 99%